Observational Burden of Illness Study in Patients With Crohn’s Disease With and Without Perianal Fistulas in the United States - Jeanne Jiang; Susan E. Cazzetta; Amod Athavale; Maja Kuharic; Tao Fan; Abigail Silber; Vijay Abilash; Nandini Hadker; Emily Sharpe; Pradeep P. Nazarey (Gastro Hep Advances, 2023)
Background and Aims: This study compared disease burden, experiences, and health-related quality of life (HRQoL) between patients with Crohn’s perianal fistulas (CPFs) and those with Crohn’s disease (CD) without perianal fistulas (PFs; non-PF CD). Methods: This cross-sectional, observational study was conducted in 3 cohorts of US patients aged 18–89 years with self-reported, physician-diagnosed CD: (1) non-PF CD; (2) CPF without PF-related surgery; and (3) CPF with PF-related surgery. Data on medical and surgical interventions, CD-specific symptoms, HRQoL (assessed using the Short Inflammatory Bowel Disease and 5-dimension EuroQol questionnaires), and fecal incontinence (assessed using Revised Faecal Incontinence Scale and Fecal Incontinence Quality of Life questionnaires) were collected via a web-enabled questionnaire. Results: In total, 403 patients with CD completed the questionnaire (non-PF CD, n = 300; CPF without surgery, n = 51; CPF with surgery, n = 52). A high symptom burden was seen across cohorts. More patients with CPF underwent ≥1 CD-related surgery and experienced ≥1 failure of CD-related surgery (79% and 20%) vs non-PF CD (53% and 9%; P < .001). Overall HRQoL outcomes were worse for patients with CPF vs non-PF CD, with significantly worse Short Inflammatory Bowel Disease and 5-dimension EuroQol questionnaire scores for those without PF-related surgery (P < .01). Across all cohorts, 58% of patients reported experiencing fecal incontinence, which had a greater negative impact (higher Revised Faecal Incontinence Scale scores; lower Fecal Incontinence Quality of Life scores) in patients with CPF vs non-PF CD. Conclusion: Patients with CPF experience substantial HRQoL burden, reflecting the impact of symptoms and medical/surgical interventions. These results may help to inform comprehensive care strategies to improve patient HRQoL.